2016
DOI: 10.1021/acs.est.6b04478
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Functional Groups on the Viscosity of Organic Aerosol

Abstract: Organic aerosols can exist in highly viscous or glassy phase states. A viscosity database for organic compounds with atmospherically relevant functional groups is compiled and analyzed to quantify the influence of number and location of functional groups on viscosity. For weakly functionalized compounds the trend in viscosity sensitivity to functional group addition is carboxylic acid (COOH) ≈ hydroxyl (OH) > nitrate (ONO) > carbonyl (CO) ≈ ester (COO) > methylene (CH). Sensitivities to group addition increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
188
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(210 citation statements)
references
References 94 publications
22
188
0
Order By: Relevance
“…Song et al (2016b) showed that estimations from group contribution approaches combined with either non-ideal or ideal mixing reproduced the RH-dependent trends particularly well for the alcohol, dicarboxylic, and tricarboxylic acid systems with viscosities of up to 10 4 Pa s. In contrast, model calculations overestimated the viscosity of more viscous compounds including monosaccharides, disaccharides, and trisaccharides by many orders of magnitude (Song et al, 2016b). A recent study compiled the viscosity of organic compounds with atmospherically relevant functional groups, investigating the influence of the number and location of functional groups on viscosity (Rothfuss and Petters, 2017a). These studies provide important insights into estimating the viscosity of individual organic compounds.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Song et al (2016b) showed that estimations from group contribution approaches combined with either non-ideal or ideal mixing reproduced the RH-dependent trends particularly well for the alcohol, dicarboxylic, and tricarboxylic acid systems with viscosities of up to 10 4 Pa s. In contrast, model calculations overestimated the viscosity of more viscous compounds including monosaccharides, disaccharides, and trisaccharides by many orders of magnitude (Song et al, 2016b). A recent study compiled the viscosity of organic compounds with atmospherically relevant functional groups, investigating the influence of the number and location of functional groups on viscosity (Rothfuss and Petters, 2017a). These studies provide important insights into estimating the viscosity of individual organic compounds.…”
Section: Introductionmentioning
confidence: 91%
“…Quasi-equilibrium versus kinetically limited or non-equilibrium SOA growth remains an open issue and warrants further investigations. Group contribution methods have been used to predict the viscosities of pure compounds when the functionality and molecular structure are known (Sastri and Rao, 1992;Rothfuss and Petters, 2017a). Song et al (2016b) showed that estimations from group contribution approaches combined with either non-ideal or ideal mixing reproduced the RH-dependent trends particularly well for the alcohol, dicarboxylic, and tricarboxylic acid systems with viscosities of up to 10 4 Pa s. In contrast, model calculations overestimated the viscosity of more viscous compounds including monosaccharides, disaccharides, and trisaccharides by many orders of magnitude (Song et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations